ANTISEPTICS RESISTANCE GENES (QACA/B, SMR) DETECTION AND EXPRESSION IN STAPHYLOCOCCUS AUREUS - A. A. Jawad; N. M. Utba (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate the resistance of S. aureus to different antiseptics.This research indicate that the resistance of S.aureus to antiseptics is due to possessing either the smr gene or the qacA/B genes that associated with decreased susceptibility to antiseptics there for this study amid to determine the frequencies of S. aureus chloroxylenol resistant isolates and the presence of the previous genes in these isolates as well as the effect of chloroxylenol on the expression of these genes.189 clinical isolates isolated from skin infections identified as S. aureus in Baghdad by microscopical and biochemical tests. The chloroxylenol resistance S. aureus isolates was identified and chloroxylenol MIC was evaluated for these isolates. Antiseptic resistance genes (qacA/B, smr) were detected by PCR method and the results reveled that 21(84%) out of 25 isolates harbored qacA/B gene. While the smr gene was not demonstrated in any isolates. Furthermore, the chloroxylenol had no effect on qacA/B gene expression in these isolates.